Farmers’ knowledge and perception of enset Xanthomonas wilt in southern Ethiopia - Z. Yemataw; A. Mekonen; A. Chala; K. Tesfaye; K. Mekonen; D. J. Studholme; K. Sharma (Agriculture & Food Security, 2017)
Abstract Background Enset Xanthomonas wilt (EXW) was first reported in 1939 and continues to threaten the sustainability of farming systems in south and southwestern parts of Ethiopia. The present study was conducted in the central zones of southern Ethiopia to assess farmers’ knowledge and perception about EXW, its etiology and mode of transmission, and its implications for the management of EXW. Methods A survey was conducted in 240 households across Hadiya, Kembata-Tembaro and Wolaita zones of southern Ethiopia using focus group discussions and a structured questionnaire to assess farmers’ perceptions of causes and modes of EXW transmission, and their knowledge on symptom identification. In addition, EXW prevalence, incidence and severity were determined for each zone. Data were analyzed through descriptive statistics. Results The results showed that a significant number of farmers are aware of EXW, its symptoms, etiology and transmission and spread, but they are not able to readily relate modes of spread to control methods. Since 2002, EXW became prominent in Hadiya, with the highest EXW incidence and severity, followed by Wolaita, and Kembata-Tembaro. Farmers identified EXW as the major cause for declining production and productivity of enset in the region. Conclusion EXW has spread widely and rapidly in southern Ethiopia, with significant socioeconomic impacts in smallholders’ livelihoods. There is a need for developing knowledge-based strategies and awareness-raising campaign for EXW management.